Eduwisata Hutan Mangrove sebagai Implementasi Sikap Cinta Lingkungan di Paluh Merbau Desa Tanjung Rejo Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Nasution, Irda Wahidah; Nasution, Nurul Hidayah (Society : Jurnal Pengabdian Masyarakat, 2023)
Mangroves are natural resources that are found in many coastal areas, mangroves as plants found in tidal areas and as communities. Mangrove forest education is an educational tour about the main ecosystems that support the life of coastal areas. Besides that, the community's ability to contribute to the development of mangrove education tourism will also affect people's income, especially in Paluh Merbau, Tanjung Rejo Village, which is part of Deli Serdang Regency, which is located in Percut Sei Tuan District. The method used is to increase student tourism education, insight and knowledge, and student competence regarding the local potential of coastal areas, especially mangrove ecosystems which have environmental service values to be managed and utilized as ecotourism areas, through community involvement and empowerment-based service. This service can increase students' love for the environment in community problems related to the use of coastal areas. The procedure for carrying out community service consists of three stages including surveys and interviews, preparation, and implementation, this activity was carried out on October 18, 2021. This community service activity was for mangrove forest education and was attended by around Â± 40 people, consisting of lecturers and students, farmer groups, and local communities, as well as the Paluh Merbau Mangrove Tourism Management Coordinator (YMAII). The theme of the assistance activities carried out is in the form of lecture activities as well as educational tours of mangrove forests which are implemented towards an attitude of love for the environment. By sharing this knowledge, it is hoped that the public will have a vehicle for creative thinking to manage tourist attractions to become educational objects so that they can attract interested tourists who come to tourist areas with the aim of not only being able to enjoy the beauty of nature but also to gain additional useful knowledge.